2022
DOI: 10.1073/pnas.2122301119
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of synaptic and cognitive capacity: Insights from the nervous system transcriptome ofAplysia

Abstract: The gastropod mollusk Aplysia is an important model for cellular and molecular neurobiological studies, particularly for investigations of molecular mechanisms of learning and memory. We developed an optimized assembly pipeline to generate an improved Aplysia nervous system transcriptome. This improved transcriptome enabled us to explore the evolution of cognitive capacity at the molecular level. Were there evolutionary expansions of neuronal genes between this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 85 publications
0
15
0
Order By: Relevance
“…Initially, we used NCBI to search specific sequences of interests. In addition, we also searched AplysiaTools databases (Dr Thomas Abrams, University of Maryland ( 58 )) to obtain additional sequences for comparison. These latter databases ( http://aplysiatools.org ) include databases for Aplysia transcriptome and Aplysia genome.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, we used NCBI to search specific sequences of interests. In addition, we also searched AplysiaTools databases (Dr Thomas Abrams, University of Maryland ( 58 )) to obtain additional sequences for comparison. These latter databases ( http://aplysiatools.org ) include databases for Aplysia transcriptome and Aplysia genome.…”
Section: Methodsmentioning
confidence: 99%
“…However, few have explored the contributions of specific residues or other properties of ligands to receptor activity based on the structure of a protostome’s receptor that has no known homologs in deuterostomes (vertebrates and some invertebrates), partly because a protein structure cannot be obtained using a homology modeling approach. In the present work, we utilize a molluscan model system, Aplysia californica ( 11 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ), to study this issue using Aplysia leucokinin peptides (ALKs) ( 60 ) and their receptor. In particular, recent successful efforts ( 14 ) have been made to predict protein structure based on the amino acid sequence of a protein, particularly template-free modeling ( 61 ) using artificial intelligence (AI) deep machine learning algorithms such as Robetta ( 62 ) and AlphaFold ( 63 ).…”
mentioning
confidence: 99%
“…A study of the Aplysia transcriptome showed that the evolutionary distance from humans to Aplysia is shorter than the distance from humans to Drosophila and C. elegans ( Moroz et al, 2006 ). Another recent comparative transcriptome study showed that Aplysia possesses synaptic proteins very similar to those of Octopus , whereas several synaptic scaffold protein families in both mollusks are missing in vertebrate lineages ( Orvis et al, 2022 ). The similarity in synaptic proteins and difference in neural network structure (separated ganglia vs. an elaborated central brain) between Aplysia and Octopus suggested that the difference in cognitive capacity is more related to the difference in neural network structure than to the lower-level differences of molecular biophysics ( Orvis et al, 2022 ).…”
Section: Differences Between Aplysia and Vertebrat...mentioning
confidence: 99%
“…Another recent comparative transcriptome study showed that Aplysia possesses synaptic proteins very similar to those of Octopus , whereas several synaptic scaffold protein families in both mollusks are missing in vertebrate lineages ( Orvis et al, 2022 ). The similarity in synaptic proteins and difference in neural network structure (separated ganglia vs. an elaborated central brain) between Aplysia and Octopus suggested that the difference in cognitive capacity is more related to the difference in neural network structure than to the lower-level differences of molecular biophysics ( Orvis et al, 2022 ). Another recent study mapped the Aplysia proteome to humans and cross-referenced it with two databases of genes of interest in Alzheimer’s disease research.…”
Section: Differences Between Aplysia and Vertebrat...mentioning
confidence: 99%
“…We sought to study an oxytocin/vasopressin signaling system in the gastropod mollusc Aplysia californica . Aplysia is an experimentally-advantageous system and has provided fundamental insight into the neural basis of motivated behaviors ( Jing and Weiss, 2002 ; Jing et al, 2004 ; Sasaki et al, 2009 ; Jing et al, 2010 ; Sasaki et al, 2013 ; Zhang et al, 2020 ; Bedecarrats et al, 2021 ; Evans et al, 2021 ; Due et al, 2022 ; Wang et al, 2023 ), learning and memory ( Sieling et al, 2014 ; Byrne and Hawkins, 2015 ; Orvis et al, 2022 ) and neuromodulation ( Cropper et al, 2018b ; Zhang et al, 2022 ), including neuropeptides ( Livnat et al, 2016 ; Zhang et al, 2017 ; Do et al, 2018 ; Zhang et al, 2018 ; Chan-Andersen et al, 2022 ) and receptors ( Bauknecht and Jekely, 2015 ; Checco et al, 2018 ; Guo et al, 2022 ; Jiang et al, 2022 ; Zhang et al, 2022 ). The first evidence for the presence of oxytocin/vasopressin-related neuropeptide in protostomes comes from an early immunohistochemical study ( Remy et al, 1979 ), and the later identification of an arginine vasopressin-like diuretic hormone ( Proux et al, 1987 ), both in insects.…”
Section: Introductionmentioning
confidence: 99%